Konflik Elite Politik Dalam Pemilihan Umum Gubernur Dan Wakil Gubernur Provinsi Maluku Utara Tahun 2007 - Husen, Rahmi (JURNAL ILMIAH SOCIETY, 2016)
This research aims at describing the conflict's political elite in the general election the Governor and Vice Governor of North Maluku province in 2007. The method of research used the qualitative method. Data was collected through in-depth interviews, direct observation, and study the documentation. The research results show that in the implementation of the general election governor and the vice governor of North Maluku 2007 found: First, conflict start seen since stage registration candidates, in which couples H. Mudaffar Syah-H. Rusdi Hanafi cancelled of his preferred candidate by KPUD provincial North Maluku because they did not fulfill regulation the 15 % to the votes and support seats. Second, stage campaign period, conflict can also be seen start hardened because third candidate couple and team the success of protest against the schedule some of which day has fallen during Ramadan and Eid, and when socialization stage the schedule is accepted all parties well. Third, calculation stage and recapitulation the ballot, where conflict is more open and prolonged caused the political elite prefer the interests of each as to be almost no space negotiations to conflict resolution. Fourth, stage conflict resolution, done through state apparatus with the approach security, negotiations, and dialogue. Although recognized, during conflict the political elite never want to sit with to dialogue in order to find resolution (handling) the conflict. Keywords : Conflict, Politic